Screening Screens: Cinematic Spectatorship in the Desktop Film Noah (Cinéma & Cie. Film and Media Studies Journal, 2020)
This article explores the effects of spectatorship in the short film Noah, a nearly 18’ desktop film created by Patrick Cederberg and Walter Woodman that premiered at the 2013 Toronto International Film Festival. My discussion progresses existing theories about the status of text in films and encourages us to rethink how Noah’s presentation of computer interfaces contributes to novel perspectives regarding the relationship between viewer and screen. Considering the computer screen’s remediation and its cinematic effects, specifically focusing on the acts of reading and watching in Noah, I propose that the remediated computer screen in Noah transforms reading into a viewable activity, thus recharacterizing text as moving image. Altogether, this article posits that, as a desktop film, Noah dismantles set connotations of screens across early and contemporary forms of new media and paves the way for contemporary cinema’s digital futures.